Effect of tetrandrine and verapamil on contractility and oxygen consumption of the heart muscles - YAO Wei-xing; XIA Guo-jin; FANG Da-chao; JIANG Ming-xing (Acta Pharmacologica Sinica, 2016)
The effects of tetrandrine (Tet) and verapamil (Ver) on contractility and oxygen consumption were compared on isolated guinea pig left atrial strips and cat papillary muscles Both drugs diminished the Ca++-dependent contractile force and the O2 consumption of electrically driven preparations. These effects were antagonized by increasing the extracellular Ca++ concentrations. Under the influence of increasing doses of Tet (52-210μM) and Ver(0.72-2.9μM) linear reduction of isometric tension and O2 consumption due to mechanical activity were seen. With Tet 0.21 mM and Ver 2.9μM the tension development and contractility-dependent O2 consumption were greatly decreased. The results indicate that Tet is an effective Ca++-antagonist very similar to Ver.